Prospects of the Role of Parents in Islamic Religious Education in the Contemporary Era - Anati Rahila (Maklumat: Journal of Da'wah and Islamic Studies, 2024)
Education is one form of investment for society in realizing intelligent and advanced successors to the nation. Islamic education itself can be interpreted as an effort to educate individuals through teaching based on Islamic values. Today there are several contemporary issue phenomena that are quite disturbing. Some of these phenomena are related to the problem of moral degradation. Several previous studies argue that religious education should be emphasized and considered as one of the educations that can erode this phenomenon. Based on this statement, of course, internalization of the values ​​of Islamic religious education in everyday life is needed. Islamic religious education can provide encouragement for someone to be able to carry out positive practices in everyday life. Such as being honest and fair, polite, devoted, and not violating the rights of others. Islamic education can run optimally if parents as one of the facilitators of education also play a role in it. Parents are the main educators for children. Parents play an important role in providing teachings to their descendants. Based on the discussion that has been presented by the author, it can be concluded that parents have an important role in Islamic Religious Education in the Contemporary Era. The statement can be seen from the role of parents in educating, protecting, guiding and teaching their children. Parents play an important role in providing religious education since early childhood. Parents have the responsibility to guide their offspring to become perfect and upright human beings according to religious ethics. Therefore, the results of this study are that parents have prospects in Islamic religious education in the contemporary era as facilitators in education.